2018
DOI: 10.1371/journal.pone.0196969
|View full text |Cite
|
Sign up to set email alerts
|

Widespread plant specialization in the polyphagous planthopper Hyalesthes obsoletus (Cixiidae), a major vector of stolbur phytoplasma: Evidence of cryptic speciation

Abstract: The stolbur phytoplasma vector Hyalesthes obsoletus is generally considered as a polyphagous species associated with numerous wild and cultivated plants. However, recent research in southeastern Europe, the distribution centre of H. obsoletus and the area of most stolbur-inflicted crop diseases, points toward specific host-plant associations of the vector, indicating specific vector-based transmission routes. Here, we study the specificity of populations associated with four host-plants using mitochondrial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 83 publications
2
45
0
Order By: Relevance
“…Adults of H. obsoletus originating from stinging nettle survived better on stinging nettle than on field bindweed and vice versa for adults from bindweed. These data confirm the results of previous studies [ 35 , 36 , 37 ] and support the hypothesis of cryptic speciation [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adults of H. obsoletus originating from stinging nettle survived better on stinging nettle than on field bindweed and vice versa for adults from bindweed. These data confirm the results of previous studies [ 35 , 36 , 37 ] and support the hypothesis of cryptic speciation [ 38 , 39 ].…”
Section: Discussionsupporting
confidence: 92%
“…Hyalesthes obsoletus adult populations collected on field bindweed and stinging nettle showed a better survival and adaptation to the originating host [ 26 , 35 , 36 , 37 ]. The genetic differences between the populations associated with these two herbaceous plants suggested the occurrence of cryptic speciation [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to microsatellite analyses, H. obsoletus populations collected in French lavenders differ from populations living on C. arvensis and U. dioica in Europe ( 30 ). H. obsoletus can locally adapt to new plant hosts, developing into plant-specialized ecotypes that can be morphologically identical but that have limited exchange with other populations living on different plants ( 31 , 32 ). It was recently shown that H. obsoletus populations developing on clary sage, a crop of the lavender plant family, had limited exchange with populations living on surrounding lavenders ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Field bindweed is one of the major and most widely distributed natural hosts and plant reservoirs of ‘ Candidatus Phytoplasma solani’ (‘ Ca. P. solani’) and its planthopper vector Hyalesthes obsoletus (Hemiptera: Cixiidae) in agroecosystems and in natural habitats of the Euro-Mediterranean area [ 2 , 3 , 4 , 5 , 6 , 7 ]. ‘ Ca.…”
Section: Introductionmentioning
confidence: 99%
“…Given the epidemiological and ecological complexity of ‘ Ca. P. solani’-induced diseases [ 6 , 7 , 8 , 19 , 20 , 21 , 22 , 23 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and its evolutionary relatedness to ‘ Ca. P. convolvuli’, the focus of this study was to analyze the (co)occurrence of the two pathogens in shared host plant and related symptoms.…”
Section: Introductionmentioning
confidence: 99%